A Study on Lug Structure at Fuselage - Wing Joint of an Unmanned Aerial Vehicle Using Finite Element Method - Cahya, Fadli; Pramana, Nurhadi; Chairunnisa; Adhynugraha, Muhammad Ilham; Aribowo, Agus; Nurrohmad, Abian (BRIN Publishing, 2023)
Research on structural analysis of an unmanned aerial vehicle (UAV) is carried out. The primary material used in most structures is carbon composite. Having a high aspect ratio wing, the lugs connecting the wing and fuselage are likely to experience maximum forces during flight tests. In predicting the occurrence of deformation and stress, the finite element method is used by applying max./min. strain criteria to evaluate the structural integrity of composite wings due to the load applied on aluminum-based lugs. The evaluation shows that the current wing configuration has good structural integrity. An optimization approach is also carried out to obtain more optimum results.